(untitled) (Bangladesh Journal of Microbiology, 2020)
Antibiotics, both broad- and narrow spectrum, are widely used for treatment of specific infection by a consortium of microorganisms or by a single pathogen, respectively. Oral or intravenous, or even topical administration of different categories of antibiotics in various forms is a common practice round the globe. Yet for the recent years a major public health issue has been raised by the emergence of the drug-resistance microorganisms. A number of researches focused on the issue of the ineffectiveness of antibiotics as well as regarding the evolution of the drugresistance genes within the pathogenic microorganisms. Isolation of the drug-resistant microorganisms including the multi-drug resistant (MDR) and the extensively drug resistant (XDR) bacteria from a range of patients with microbiological infections has been seriously challenging the disease mitigation approaches. Besides, the dominance of the methicillin resistant Staphylococcus aureus (MRSA), vancomycin resistant Staphylococcus aureus (VRSA), etc. are quite frequent as evident from different case studies. Current review focused on the origin and evolution of such drug-resistance incidences, and the promising remedies over the problems of drug-resistance. Bangladesh J Microbiol, Volume 36 Number 2 December 2019, pp 111-114